On-line power quality monitoring system using compactRIO device: a review on system development - Ab Kadir, Mohd Zainal Abidin; Tuan Othman, S. S.; Lombigit, Lojius (EuroJournals, 2008)
Power quality is an important issue in the power system. If power quality problem occurred, the effects such as manufacturing interruptions, loss of production, loss of revenue, lost of opportunities, product damage, and wasted energy and decreased equipment life will significantly be affected. One of the ways to detect the power quality problem is by on-line monitoring. This monitoring can be done by accessed to the point address in networking and those who involved in this site can go through for a quick assessment. This paper comprises of modelling the system, which is developed in LabVIEW environment and integrated using a powerful CompactRIO system. Detail of the modules and integration process are presented, together with the initial result obtained from data monitoring.